Purification and recycling of municipal wastewater based on MBR process. (5th March 2022) - Jiang, Zhongfeng; Gao, Hongbin; Wu, Li; Li, Yanan; Cui, Bifeng
In order to overcome the problems of low purification efficiency and recycling efficiency in traditional municipal wastewater purification and recycling methods, a new municipal wastewater purification and recycling method based on MBR process is proposed in this paper. This paper analyses the principle of MBR process, applies MBR to the design of municipal sewage purification treatment device, uses the device to filter macromolecular pollutants, and realises the municipal sewage purification treatment. Based on the purified municipal wastewater, the municipal wastewater was recycled from three aspects: pH adjustment, phosphorus precipitant selection and sediment SEM analysis. The experimental results show that, compared with the traditional method, this method has higher efficiency of municipal sewage purification and higher recovery rate of water resources, and the total cost of sewage purification and recycling is lower, and the comprehensive benefits are better.